2005
DOI: 10.1128/jvi.79.19.12342-12354.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Activities between Herpes Simplex Virus Type 1 Regulatory Protein ICP0, a Ubiquitin E3 Ligase, and Ubiquitin-Specific Protease USP7

Abstract: Herpes simplex virus type 1 (HSV-1) regulatory protein ICP0 stimulates lytic infection and the reactivation of quiescent viral genomes. These roles of ICP0 require its RING finger E3 ubiquitin ligase domain, which induces the degradation of several cellular proteins, including components of promyelocytic leukemia nuclear bodies and centromeres. ICP0 also interacts very strongly with the cellular ubiquitin-specific protease USP7 (also known as HAUSP). We have shown previously that ICP0 induces its own ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
131
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 42 publications
8
131
0
Order By: Relevance
“…USP7, which appeared as a nuclear protein in the absence of ICP0 (Figure 4Aiii) translocated to a perinuclear compartment when coexpressed with wt-ICP0 (Figure 4Av). In agreement with previous studies showing that USP7 undergoes proteasomal degradation by ICP0, 37 we detected reduced levels of USP7 in cells coexpressing wt-ICP0 (Figure 4Av). ICP0-NLS-MUT failed to alter USP7 localization.…”
Section: Icp0 Alters Cellular Localization Of Usp7supporting
confidence: 93%
“…USP7, which appeared as a nuclear protein in the absence of ICP0 (Figure 4Aiii) translocated to a perinuclear compartment when coexpressed with wt-ICP0 (Figure 4Av). In agreement with previous studies showing that USP7 undergoes proteasomal degradation by ICP0, 37 we detected reduced levels of USP7 in cells coexpressing wt-ICP0 (Figure 4Av). ICP0-NLS-MUT failed to alter USP7 localization.…”
Section: Icp0 Alters Cellular Localization Of Usp7supporting
confidence: 93%
“…In subsequent studies on the role of ubiqiuitin-specific protease 7, the same laboratory showed for the most part narrow strips containing full-length ICP0 only (14,15). They concluded that the protease blocks degradation of ICP0 by proteasome dependent pathway, presumably the proteasome-dependent pathway reported here.…”
Section: Discussionmentioning
confidence: 49%
“…21,25,26 To further understand the mechanism of Daxx-based mitosis progression and taxane resistance, we employed proteomic approach to isolate the Daxx mitotic complex and characterize Daxx-interacting proteins. Here we report that ubiquitin (Ub)-specific processing protease-7 (USP7), 27 a deubiquitylating enzyme, is a Daxx-interacting protein in mitosis. USP7 interacts with and stabilizes the mitotic checkpoint protein E3 Ub ligase CHFR (checkpoint with forkhead and Ring-finger), 28 but USP7 direct involvement in mitotic regulation has not yet been demonstrated.…”
mentioning
confidence: 99%